Sosialisasi di SMK Kesehatan Pro-Skill Indonesia: Membangun Generasi Cerdas Finansial dan Perlindungan Keuangan - Christin Tabita Putri Manurung; Jesi Rahmadhani; Thessa Natalia Laia; Hayati Nufus Syakirah; Ari Rizki Pratama S; Aziz Aulia Rahman; Magdalena Wati Tamba; Muhammad Rifqi Yafiq; Mutiara Ananda Rizqi; Shaula Alifaturrosidah; Syarifah Rahmah (Unri Conference Series: Community Engagement, 2025)
The low level of financial literacy in Indonesia remains a serious issue, as many people are still frequently trapped in illegal investments, online loans, and online gambling. Therefore, this study conducted a financial literacy outreach program for SMK students, who are mostly about to enter the workforce and are considered highly vulnerable to external influences. The program aimed to educate students to become smarter in managing their finances, recognizing the characteristics of illegal investments, and understanding the risks of online loans and gambling. This research employed a mixed-method approach, combining a quantitative design through pre-test and post-test with a qualitative approach through direct observation during the program.The results of this study showed a significant difference, where there was an increase of 9.09% after the presenter explained.Therefore, this outreach activity proved to be highly effective in enhancing the financial literacy of SMK Kesehatan Pro-Skill Indonesia students and is expected to provide them with valuable knowledge to manage their finances more wisely in the future.